Uterine-sparing surgery for adenomyosis and/or adenomyoma - Huann-Cheng Horng; Ching-Hui Chen; Chih-Yao Chen; Kuan-Hao Tsui; Wei-Min Liu; Peng-Hui Wang; Wen-Hsun Chang; Ben-Shian Huang; Hsu-Dong Sun; Ting-Chang Chang; Wei-Chun Chang; Ming-Shyen Yen (Elsevier, 2014)
Adenomyosis of the uterus is defined as the presence of endometrial tissue, including glands and stroma, situated at least 2.5 mm below the endometrial-myometrial junction and widely distributed within the myometrium layer of the uterus. There is no consensus on the appropriate treatment for symptomatic uterine adenomyosis in women who want to preserve their uterus, partly because adenomyosis is somewhat enigmatic in diagnosis and owing to its clinical significance. Hysterectomy, through either exploratory laparotomy or minimally invasive procedures, is a definite treatment for uterine adenomyosis, once the women have completed childbirth or do not require future fertility. However, many women with a uterine pathology still have a strong desire to preserve the uterus, for which conservative and uterine-sparing procedures are increasingly used, and with which fertility preservation or quality-of-life improvement can be achieved. Although medical management can be effective, similar to the management of uterine fibroids (myoma), its effect is often transient and rapid regrowth of adenomyosis and relapse of symptoms and signs always occur once the treatment is stopped. Therefore, other strategies should be selected. Conservative and uterine-sparing surgery might be one of the most familiar procedures of these uterine-sparing procedures. In this article, the latest knowledge and research evidence on uterine-sparing surgery for uterine adenomyosis are reviewed.